Pedagogical practices for the reconstruction of the social fabric in conflict territories - Quimbayo-Feria, Adriana; Gutiérrez, Andrés; Cruz Ortiz, Elvira; López, Angi; Rivas, Lusana; Leon, Aida; Ortega, Ana; Arco Mosquera, Lucy (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This research recognizes peace as a scenario in which conflict is present and in which the different positions must learn to coexist. To do this, the question is raised: How have the pedagogical practices of teachers and professors transformed in the last 20 years for the reconstruction of the social fabric in territories affected by the armed conflict in Colombia? These practices seek to mediate the relationships between individuals and their tensions, teaching resilience and the ability to mitigate the negative effects that expressions of violence can have on the development of young people who live in this context.